PENERAPAN PERMOHONAN DISPENSASI KAWIN DI PENGADILAN NEGERI DENPASAR PASCA PERMA N0 5 TAHUN 2019 ANTARA PERLINDUNGAN ANAK DAN REALITAS SOSIAL - Putu Suria Dewi; Suwarjo; Ratna Artha Windari (Jurnal Ilmu Hukum Sui Generis, 2026)
Marriage signifies a lifelong bond between a man and a woman, legally and religiously regulated in accordance with the couple's intentions and applicable rules, and maintained throughout their lives within the institution of marriage (Tuti, 2006). According to Thalib (1996), marriage is a sacred and binding agreement for a man and a woman to live together legally, with the hope of building an enduring family characterized by mutual respect, love, peace, and happiness. The amendment of Law Number 1 of 1974 by Law Number 16 of 2019 established a minimum marriage age of 19 for both men and women, an effort aimed at protecting children's rights and curbing early marriage rates. Nevertheless, the provisions for marriage dispensation—as regulated by Supreme Court Regulation (PERMA) Number 5 of 2019—still allow for underage marriages through court rulings based on urgent grounds. This study aims to analyze the handling of marriage dispensation applications at the Denpasar District Court following the enactment of PERMA Number 5 of 2019, specifically regarding child protection, and to identify the challenges faced and potential solutions. The study employs an empirical legal research method with a qualitative approach. Primary data were obtained through observation and interviews with Denpasar District Court officials, while secondary data were derived from relevant legislation, literature, and scientific journals. The findings indicate that judges have applied the principle of the "best interests of the child" by assessing psychological, health, and physical readiness aspects, as well as social conditions and the child's future, prior to granting a marriage dispensation. However, implementation still faces various obstacles, such as the public's limited legal understanding, difficulties in proving "urgent grounds," the practice of marriage occurring prior to the court ruling, socio-cultural pressures, and administrative hurdles. Therefore, it is necessary to strengthen the capacity of judges, foster inter-agency synergy, provide psychological assessment services, and conduct continuous outreach so that marriage dispensations truly serve as an instrument for child protection and are granted only in highly urgent circumstances, in accordance with the principle of the best interests of the child.